2020
DOI: 10.1101/2020.04.22.20074351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resilient SARS-CoV-2 diagnostics workflows including viral heat inactivation

Abstract: There is a worldwide shortage of reagents to perform detection of SARS-CoV-2. Many clinical diagnostic laboratories rely on commercial platforms that provide integrated end-to-end solutions. While this provides established robust pipelines, there is a clear bottleneck in the supply of reagents given the current situation of extraordinary high demand. Some laboratories resort to implementing kit-free handling procedures, but many other small laboratories will not have the capacity to develop those and/or will p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Buccal swabs obtained during the home visits were used to test for current SARS-CoV-2 RNA (and by inference active replication) using RT-PCR as previously described by Lista et al 10 Briefly, nasopharyngeal swab samples were heat inactivated at 70 °C for 30 min and 140 μl were used to extract RNA with the Beckman Coulter RNAdvance Blood kit, ending with elution in 50 μL of water. For qPCR, the US CDC designed primer/probe set were used for the N gene (N1 and N2) and RNAseP with 5 μL of RNA sample and Taqman Fast Virus 1-Step Master Mix (Thermofisher).…”
Section: Testing For Active the Presence Of Sars-cov-2mentioning
confidence: 99%
“…Buccal swabs obtained during the home visits were used to test for current SARS-CoV-2 RNA (and by inference active replication) using RT-PCR as previously described by Lista et al 10 Briefly, nasopharyngeal swab samples were heat inactivated at 70 °C for 30 min and 140 μl were used to extract RNA with the Beckman Coulter RNAdvance Blood kit, ending with elution in 50 μL of water. For qPCR, the US CDC designed primer/probe set were used for the N gene (N1 and N2) and RNAseP with 5 μL of RNA sample and Taqman Fast Virus 1-Step Master Mix (Thermofisher).…”
Section: Testing For Active the Presence Of Sars-cov-2mentioning
confidence: 99%
“…If sufficiently characterized for screening, this and other newly developing approaches could allow for more rapid and less reagent intensive virologic analysis of swabbed samples than the standard RT–PCR testing approaches that have been broadly employed for COVID testing (e.g., the majority of in vitro diagnostic tests receiving an Emergency Use Authorization (EUA) approval from the US FDA and/or are recommended by health authorities in other countries rely on RT–PCR methods with an RNA extraction step). Some of these labs are also exploring means to partially or totally inactivate the virus just after swab collection in order to increase the throughput of these more rapid RT – PCR methods and expand the number of labs eligible to process samples (preprint: Lista et al , ). Optimization of sampling procedures via protocols for alternative swabs and sampling media may also contribute to the propagation of testing via rapid RT – PCR or other means.…”
Section: Pillars For Actionmentioning
confidence: 99%
“…COPAN™, another VTM, is registered as a non-propagating transport and culture medium with the FDA but does not contain any inactivating agents [ 11 ]. To date, there have been nine studies that have evaluated chemical inactivating ingredients and shown effective virucidal activity against SARS-CoV-2 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], but to our knowledge there has been no evaluation of commercially available VTMs that could be utilized in an appropriate workflow for community-based molecular POC testing.…”
Section: Introductionmentioning
confidence: 99%